2008
DOI: 10.1021/cb800012x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Fluctuations in Plasma Membrane Vesicles

Abstract: We demonstrate critical behavior in giant plasma membrane vesicles (GPMVs) that are isolated directly from living cells. GPMVs contain two liquid phases at low temperatures and one liquid phase at high temperatures and exhibit transition temperatures in the range of 15 to 25 degrees C. In the two-phase region, line tensions linearly approach zero as temperature is increased to the transition. In the one-phase region, micrometer-scale composition fluctuations occur and become increasingly large and long-lived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
508
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(564 citation statements)
references
References 35 publications
51
508
5
Order By: Relevance
“…S5A), the vesicles probably contain pre-existing nanoscopic domains in a microscopically uniform phase as previously suggested by Baumgart et al and others (25,42). Indeed, recent reports propose that GPMVs have a composition close to a critical point at which a decrease in temperature coalesces pre-existing nano-domains into a microscopic phase (43).…”
Section: Analysis Of Phase Separation In Plasma Membranessupporting
confidence: 72%
“…S5A), the vesicles probably contain pre-existing nanoscopic domains in a microscopically uniform phase as previously suggested by Baumgart et al and others (25,42). Indeed, recent reports propose that GPMVs have a composition close to a critical point at which a decrease in temperature coalesces pre-existing nano-domains into a microscopic phase (43).…”
Section: Analysis Of Phase Separation In Plasma Membranessupporting
confidence: 72%
“…Some researchers claim that the biomembrane is a 2D near-critical fluid mixture. [14][15][16] The influence of the near-criticality on the relaxation of the concentration fluctuation has been studied theoretically [17][18][19][20] and experimentally. 21) The author was recently involved in calculating the drag coefficient of a rigid spherical particle in a 3D near-critical binary fluid mixture, which is not very close to the critical point and is in the homogeneous phase far from the particle.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Using an artificial multicomponent membrane with a vesicle shape of several microns in size, i.e., as large as a typical cell, some experimentalists studied the line tension below the critical point and the concentration fluctuation above it. 4) They suggested that the critical concentration fluctuation be involved with the raft formation; 5) a larger correlation length near the critical point could explain the restricted raft size in the biomembrane. Concentration fluctuation also influences the deuterium nuclear magnetic relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…3, while our calculation procedure and results are shown in Sect. 4. Its last subsection gives numerical results and discussion on them.…”
Section: Introductionmentioning
confidence: 99%